2015
DOI: 10.1371/journal.pone.0117117
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Study and Comparison of Caecal Methanogenesis and Fermentation Pattern in the Brown Hare (Lepus europaeus) and Domestic Rabbit (Oryctolagus cuniculus)

Abstract: The brown hare and the domestic rabbit are mid-sized herbivorous mammals and hindgut fermenters, though their digestive physiologies differ in some traits. The objective of this study was to estimate and compare the caecal microbial activity in hares and rabbits via an analysis of the following end-products of in vitro caecal fermentation: methane, total gas production, short chain fatty acids and ammonia concentration. Hare caecal methanogenesis occurred at a much lower level (0.25 mmol/kg for samples incubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 36 publications
3
14
0
Order By: Relevance
“…Similar results were obtained by Miśta et al (2015) who found that the gas production of wheat bran in rabbit equalled 37.9 ml · 0.5 g -1 (90.96/1.2 g). Whereas Bovera et al (2006) estimated in rabbits the potential gas production at 86 ml · 0.5 g -1 and 155 ml · 0.5 g -1 for dehydrated lucerne meal and beet pulp, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Similar results were obtained by Miśta et al (2015) who found that the gas production of wheat bran in rabbit equalled 37.9 ml · 0.5 g -1 (90.96/1.2 g). Whereas Bovera et al (2006) estimated in rabbits the potential gas production at 86 ml · 0.5 g -1 and 155 ml · 0.5 g -1 for dehydrated lucerne meal and beet pulp, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…The distinctive feature of the rabbit SCFA profile is that the molar proportion of butyrate exceeded that of propionate, what is opposite that in most herbivorous and omnivorous mammals, which produce more propionate than butyrate in their digestive tract (Bergman 1990). In our previous study (Miśta et al 2015), lower SCFA production was found in the hare caecum compared to in the rabbit caecum, and it was explained by the lower digestibility of hemicelluloses in the hare (Stott 2008). In the present study, the total SCFA concentration was still lower in the hares regardless of the supplementary substrate, which was either rich in hemicelluloses (wheat bran) or rich in non-structural carbohydrates with a higher fat level (oat bran).…”
Section: Caecal Fermentation Profilesupporting
confidence: 45%
“…These differences were mainly focused on total SCFA concentration, which was higher in rabbits compared to hares, as well as the propionate/butyrate ratio, which was higher in hares than in rabbits. In our previous experiments, the most surprising result was that methane production was very low in hare caecal samples compared to those of rabbits, and we established that caecal methanogenesis in the hare remained very low despite the addition of substrate into inoculums (Miśta et al 2015). However, the impact of diet, which differed between rabbits and hares, on the variations in the products of microbial activity between species was uncertain.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…The total concentration of SCFAs measured in the large intestine of the species studied so far fitted within the range of 30-240 mM, but most commonly averaged 70-120 mM (Bergman 1990;Mista et al 2015;Pecka-Kielb et al 2016). There are no published data concerning fermentation processes in WBPHs, so we compared our results to the values obtained for pigs, as the closest relatives of these animals.…”
Section: Resultsmentioning
confidence: 85%